Answer:
Explanation:
Given that,
v(t) = A + B•sin(ωt)
Then,
When t = 0 v(t)= 7
7 = A + B•Sin(ω×0)
7 = A + B•Sin0
7 = A
Then,
A = 7
v = 7 + B•sin(ωt)
So,
When t = 3, v(t) = 9
v = A + B•sin(ωt)
9 = 7 + B•Sin(3w)
9-7 = B•sin(3ω)
B•sin(3w) = 2. Equation 1
Also, at t = 6 v(t) = 7, at this point, when it returns back to7, it has complete one oscillation
v = A + B•sin(ωt)
7 = 7 + B•Sin(6w)
7-7 = B•sin(6ω)
B•sin(6w) = 0
Sin(6w) = 0 / B
Sin(6w) = 0
Take arcsin of both sides
6w = Sin~1(0)
6w = π, since it has complete one oscillation
Then, w = π /6
w = π/6
Then,
v(t) = 7 + B•Sin(πt/6)
From equation 1
B•sin(3w) = 2.
B•Sin(3 × π/6) = 2
B•Sin(½π) = 2
B = 2
Then,
v(t) = A + B•sin(ωt)
A = 7, B = 2 and w = π/6
v(t) = 7 + 2•sin(πt/6)